Underground violence: on the nature of terrorism - Calle, Luis de la (Oxford scholarship online, 2024)
Offers a comprehensive conceptual analysis of terrorism, comparing it with competing theories and views on the subject, such as terrorism is killing civilians, or terrorism is a form of violence that relies on the distinction between direct and indirect targets.